(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines the factors influencing the intention of students of the Faculty of Creative Design and Digital Business at ITSNU Pekalongan to use the Quick Response Code Indonesian Standard (QRIS) as a digital payment system. The research employs a quantitative explanatory design with a population of 317 students and a purposive sample of 80 respondents. Data were collected via a Likert-scale questionnaire and analyzed using SPSS (version 67) through t-tests, F-test, and multiple linear regression. The results indicate that Knowledge (t = 3.086, p = 0.003), Perceived Benefits (t = 5.444, p < 0.001), and Perceived Risk (t = 2.473, p = 0.016) each have a positive and statistically significant effect on students’ intention to use QRIS. The regression model is significant overall (F = 84.753, p < 0.001) and explains 76.1% of the variance in usage intention (Adjusted R² = 0.761). These findings suggest that strengthening user knowledge, emphasizing tangible benefits, and effectively managing perceived risks are crucial strategies to enhance QRIS adoption among university students. The study contributes empirical evidence to the literature on digital payment adoption and offers practical implications for policymakers, payment providers, and campus administrators seeking to increase QRIS uptake.